Semiconductor Membrane Exfoliation: Technology and Application - Hongliang Chang; Yanqing Jia; Tae‐Yong Park; Xu Zhang; Qiaoqiang Gan; Zhenqiang Ma; Tien Khee Ng; Boon S. Ooi (Advanced Electronic Materials)
Abstract Flexible semiconductor film‐based optoelectronic devices have garnered significant attention in emerging fields such as the Internet of Things (IoT), wearable devices, and smart healthcare due to their wide range of applications. It is challenging to directly grow the foundational materials of optoelectronic devices, specifically semiconductor thin film structures, on flexible substrates. Instead, they are typically fabricated on conventional rigid thick semiconductor substrates. Consequently, the exfoliation and transfer of epitaxial semiconductor thin film structures onto substrates constitute pivotal steps in the production of flexible optoelectronic devices. The integration of hard inorganic semiconductor materials with flexible substrates offers a solution to the limitations of rigidity and brittleness associated with conventional optoelectronic devices and can be used to address challenges from design to manufacturing. This review provides a comprehensive overview of the working principles and recent advances of various techniques aimed at achieving the membrane exfoliation and transfer of semiconductor structures on conventional rigid substrates. It also reviews the possible applications of the transferred membrane in a variety of optoelectronic devices. Finally, it offers insights into the potential of high‐end semiconductor manufacturing and flexible semiconductor devices to play a critical role in advancing next‐generation optoelectronics technologies.